Serum ciliary neurotrophic factor levels in children with attention deficit hyperactivity disorder - Buyuktaskin, Dicle; Guney, Esra; Gulbahar, Ozlem; Ozaslan, Ahmet; Arslan, Burak (International journal of neuroscience, 2024)
Purpose/aim of the study: The study aimed to highlight the possible role of ciliary neurotrophic factor (CNTF) in the pathophysiology of attention deficit hyperactivity disorder (ADHD) and determine whether CNTF can be used as a biomarker for ADHD.Materials and methods: Patients with a diagnosis of ADHD and neurotypical subjects aged 6-12 years were recruited prospectively. The study applied Conners' Teacher Rating Scale (CTRS) to determine the patients' ADHD predominance and severity. Serum CNTF levels were measured with an enzyme-linked immunosorbent assay (ELISA) kit.Results: A total of 43 ADHD patients and 33 healthy controls were included in the study. A significant difference was found between the serum CNTF levels of the ADHD patients (22.17 pg/ml) and the controls (22.80 pg/ml). Correlations between the CNTF levels and CTRS scores were not significant.Conclusions: The study identified an alteration of serum CNTF levels in ADHD patients and thus asserted a link between CNTF and ADHD pathophysiology; children with ADHD had significantly lower serum CNTF levels compared to the neurotypical controls. Further research is needed to understand the mechanisms of CNTF.